Engineering of a thermostable alcohol dehydrogenase towards imine reduction - Nethercott, Alanna Mary (2018)
The enantioselective reduction of carbon-nitrogen double bonds is a powerful tool for accessing chiral secondary amines. These are important building blocks in the production of many high-added value chemicals, with an estimated 40-45 % of all pharmaceuticals and 20 % of agrochemicals containing a chiral amine intermediate. However, most of their current methods of manufacture are inefficient and wasteful. As a consequence, there is an interest to develop better synthetic routes to chiral amines based on the use of catalytic technologies and of atom efficient reagents. One approach is with the use of enzymes, due to their high activities and selectivities, mild reaction conditions and their renewable origin. The enzymatic reduction of imines is a relatively recent area of research, and the known imine reductases (IREDs) have low activities and limited substrate scope. The research presented here investigates new routes to make imine reduction biocatalysts, whereby an alcohol dehydrogenase is used as a starting point to engineer reaction promiscuity. These enzymes catalyse the reduction of a similar functionality, the carbon-oxygen double bond. The mode of substrate activation differs between the two enzymes: a Brønsted acid is used in imine reductases, while a zinc(II) Lewis acid is used in alcohol dehydrogenases.